Financial Literacy Level of Students Majoring in Accounting, Mercu Buana University of Yogyakarta - Paramitalaksmi, Ratri (Interdisciplinary Social Studies, 2022)
Background: The implementation of education in improving understanding of finance in the community, especially students, is needed. Financial literacy is very closely related to financial management where the higher the financial literacy of an individual, the better his/her financial management. Aim: This research aimed to analyze the level of financial lliteracy of accounting students in Mercu Buana University of Yogykarta. Method: This study took a sample of 100 students of the Department of Accounting, Faculty of Economics, Mercu Buana University of Yogyakarta class 2019-2021. Data collection using Google Form instruments distributed to 100 respondents. Descriptive analysis method to get an overview of the level of financial literacy of students of the Department of Accounting, Faculty of Economics, Mercu Buana University of Yogyakarta class 2019-2021. Findings: From the above results, the financial literacy of students of the Department of Accounting, Faculty of Economics, Mercu Buana University of Yogyakarta is in the moderate category, namely students have knowledge and are quite skilled in managing their personal finances.